Pelvic Muscle Rehabilitation: A Standardized Protocol for Pelvic Floor Dysfunction - Rodrigo Pedraza; Javier Nieto; Sergio Ibarra; Eric M. Haas (Advances in Urology)
Introduction. Pelvic floor dysfunction syndromes present with voiding, sexual, and anorectal disturbances, which may be associated with one another, resulting in complex presentation. Thus, an integrated diagnosis and management approach may be required. Pelvic muscle rehabilitation (PMR) is a noninvasive modality involving cognitive reeducation, modification, and retraining of the pelvic floor and associated musculature. We describe our standardized PMR protocol for the management of pelvic floor dysfunction syndromes. Pelvic Muscle Rehabilitation Program. The diagnostic assessment includes electromyography and manometry analyzed in 4 phases: (1) initial baseline phase; (2) rapid contraction phase; (3) tonic contraction and endurance phase; and (4) late baseline phase. This evaluation is performed at the onset of every session. PMR management consists of 6 possible therapeutic modalities, employed depending on the diagnostic evaluation: (1) down-training; (2) accessory muscle isolation; (3) discrimination training; (4) muscle strengthening; (5) endurance training; and (6) electrical stimulation. Eight to ten sessions are performed at one-week intervals with integration of home exercises and lifestyle modifications. Conclusions. The PMR protocol offers a standardized approach to diagnose and manage pelvic floor dysfunction syndromes with potential advantages over traditional biofeedback, involving additional interventions and a continuous pelvic floor assessment with management modifications over the clinical course.